Biological chemistry laboratory practices in higher education: case analysis and improvement suggestions - Elisa Vezza, Mariana (2022)
In this article, the laboratory practices (PL) implemented in   Biological   Chemistry   I   during  the   second   year   of Microbiology,  a  university  course  offered  by  the  UNRC in  Argentina,  are  reviewed.  The  hypothesis  that  the  PL do  not  reflect  an  adequate  image  of  scientific  activity and  knowledge  is  addressed.  For  this,  the  PL  guidelines are  described    and    analyzed    through    a    qualitative methodological  approach.  The  results  agree  with  the hypothesis,  so  suggestions  are  proposed  to  restructure the PL.